Toward the Development of a Pan-Lyssavirus Vaccine - Sabrine Ben Hamed; Jacob F. Myers; Anisha Chandwani; Christoph Wirblich; Drishya Kurup; Nir Paran; Matthias J. Schnell (Viruses, 2024)
In addition to the rabies virus (RABV), 16 more lyssavirus species have been identified worldwide, causing a disease similar to RABV. Non-rabies-related human deaths have been described, but the number of cases is unknown, and the potential of such lyssaviruses causing human disease is unpredictable. The current rabies vaccine does not protect against divergent lyssaviruses such as Mokola virus (MOKV) or Lagos bat virus (LBV). Thus, a more broad pan-lyssavirus vaccine is needed. Here, we evaluate a novel lyssavirus vaccine with an attenuated RABV vector harboring a chimeric RABV glycoprotein (G) in which the antigenic site I of MOKV replaces the authentic site of rabies virus (RABVG-cAS1). The recombinant vaccine was utilized to immunize mice and analyze the immune response compared to homologous vaccines. Our findings indicate that the vaccine RABVG-cAS1 was immunogenic and induced high antibody titers against both RABVG and MOKVG. Challenge studies with different lyssaviruses showed that replacing a single antigenic site of RABV G with the corresponding site of MOKV G provides a significant improvement over the homologous RABV vaccine and protects against RABV, Irkut virus (IRKV), and MOKV. This strategy of epitope chimerization paves the way towards a pan-lyssavirus vaccine to safely combat the diseases caused by these viruses.